2012
DOI: 10.4021/wjnu5e
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bisphosphonates in Chronic Kidney Disease

Abstract: The primary goal of treatment for post-menopausal osteoporosis (PMO) is reduction in fracture risk. Therefore, bisphosphonates (BF) are the most commonly used drugs for the treatment of osteoporosis. Because of their urinary elimination, bisphosphonates must be carefully administered in chronic kidney disease (CKD) patients. Renal toxicity seems different among these compounds, and it is basically due to their protein binding and the average lifespan of renal tissues. In practice, renal toxicity has been assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous studies were conducted that reported the efficacy of pamidronate and bisphosphonates in general for the treatment of hypercalcemia in oncology patients, but these patients did not have renal impairment [ 4 , 5 ]. There are other studies about the use of bisphosphonates in renal failure, but there is very little information about pamidronate [ 6 , 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies were conducted that reported the efficacy of pamidronate and bisphosphonates in general for the treatment of hypercalcemia in oncology patients, but these patients did not have renal impairment [ 4 , 5 ]. There are other studies about the use of bisphosphonates in renal failure, but there is very little information about pamidronate [ 6 , 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are additional treatment regimens according to the correlating etiology, some of which include calcitonin and bisphosphonates. A literature search was conducted, showing theoretical evidence based on a pharmacokinetics study, which showed that pamidronate may be used in patients with renal failure based on theoretical pharmacokinetics data [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…30 Some clinicians have advocated dosage adjustments for these patients, 31 including recommendations to reduce the oral bisphosphonate dose by half. 32 However, there is little evidence to support such recommendations. Unfortunately, long-term pharmacokinetic studies looking at the outcomes of bisphosphonate dosage adjustment in CKD are not available, 33 which may be due in part to potential liability associated with studying a contraindicated use, the complexity of this patient population, and the existence of other, more urgent health priorities for patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Hamdy et al, 75% of pre-dialysis CKD patients had abnormal bone histology (74% osteitis fibrosa, 19% mixed bone disease, 1% osteomalacia, 1% aluminium bone disease, 5% a dynamic bone disease), without clinical, biochemical or radiographic evidence of bone disease [4]. Factors that predispose to low bone mineral density (BMD) in patients with CKD are age, gender, the onset of menopause, sedentary life style, low calcium intake, vitamin-D deficiency and hyperparathyroidism [5].…”
Section: Introductionmentioning
confidence: 99%